Mimicking the cochlea with an active acoustic metamaterial. (10th September 2019) - Rupin, Matthieu; Lerosey, Geoffroy; de Rosny, Julien; Lemoult, Fabrice
Abstract: The human ear is a fascinating sensor, capable of detecting pressures over ten octaves of frequency and twelve orders of magnitudes. Here, following a biophysical model, we demonstrate experimentally that the physics of a living cochlea can be emulated by an active one-dimensional acoustic metamaterial. The latter solely consists on a set of subwavelength active acoustic resonators, coupled to a main propagating waveguide. By introducing a gradient in the resonators' properties, we establish an experimental set-up which mimics the dynamical responses of both the dead and the living cochleae: the cochlear tonotopy as well as the low-amplitude sound amplifier are reproduced.